Efektifitas penggunaan media pembelajaran kreatif dalam mengatasi masalah absensi siswa - Utomo, Bagus Satrio Budi (Maliki Interdisciplinary Journal, 2024)
The use of learning media in a school institution is currently very varied, the use of information technology to support the learning process is very common in an era like today, but the problems that have long existed in the world of education in Indonesia are the problem of student motivation or interest in learning. which is lacking. This is where teaching staff are required to create a learning process that is as interesting as possible with the aim that students' learning motivation can increase. In an era that is all about using technology like now, the use of technology is certainly very helpful in teaching and learning activities, but technology-based creative learning media must also be used. requires creative and innovative teaching staff so that learning objectives can be achieved.